Controls on T-cell receptor phosphorylation and triggering - Fernandes, R (2011)
An effective immune response in mammalian cells relies on a network of molecular interactions to detect and respond to pathogens. The T-cell receptor (TCR) is one of the most important components of this system responsible for the outcome of the immunological response. Paramount to its role is its ability to efficiently signal a productive interaction with a peptide embedded in an MHC molecule. Important aspects of TCR structure and organization are unknown, limiting the current understanding of this process and rendering it highly controversial. The work described in this thesis seeks to define the valency, structural organization and signalling properties of the TCR in order to provide a better framework for thinking about the receptor-triggering problem. The results suggest that a largely monovalent complex diffuses at the surface of T cells, which is able to trigger intracellular signalling in the absence of large structural rearrangements of the extracellular subunits of the TCR. Moreover, a recently proposed mechanism involving conformational rearrangements of the cytoplasmic domains of the complex is shown to fail to explain the regulation of TCR phosphorylation. Steps are also taken toward investigating the role of more subtle conformational rearrangements at atomic resolution. Finally, an investigation of what controls tyrosine phosphorylation of the receptor in resting T lymphocytes led to the development of new approaches to address the role of specific phosphatases. The outcome of this analysis suggested how a finely-tuned balance between kinase and phosphatase activity, at both global and local levels, regulates TCR phosphorylation and T-cell activation.